The Analysis of Practices - Harré, Rom (Cambridge Scholars Publisher, 2019)
We can think of our lives as an interlinked mosaic of practices. A practice is an activity by which a practical task is accomplished according to shared standards of adequacy. Many, if not most such tasks, become routine. They are accomplished smoothly, or even inattentively: unlocking the front door, playing tennis, successfully cheating at cards, drawing hot, wet blood to cure a fever, and so on and so on. However, what must we know or presuppose in order to accomplish these tasks?This book proposes six bodies of knowledge and skill, under the generic concepts of practices and their associat.